Judaism in the Roman world : collected essays - Goodman, Martin, 1953- (Ancient Judaism and Early Christianity, 2007)
Judaism in the Roman World deals with the religious lives of Jews in the Roman world from late Second Temple times to the Later Roman Empire. *** The studies collected here analyse a series of issues important in the development of Judaism in this period: the role of the Temple and pilgrimage in the first century CE; the attitude of Jews to the physical texts of the Torah and to the scribes who produced them; the extent of variety and change within Judaism before and after 70 CE and the nature of the evidence for particular types of Judaism; the role of synagogues and images in Jewish worship; and relations between Jews and Christians in the early centuries. *** This book should be particularly useful to students of ancient Judaism and those interested in Christian origins.